Examining reading levels in ELT course books and the benefits of extensive reading - Peter Tze-Ming Chou, (Penerbit Universiti Kebangsaan Malaysia, 2011)
This study examines the difficulty level of texts in the reading sections of the Touchstone series of ELT course books. The information analyzed in the reading section included the total number of words and sentences in each reading passage, average number of sentences per paragraph, average number of words per sentence, and number of passive sentences in each text. In addition, the Flesch-Kincaid Reading Grade was used to show the Flesch Reading Ease Level and the Reading Grade Level of each reading passage. The results showed that the average number of sentences per paragraph, for each of the reading sections, was quite low. It meant that the students were not reading material with fully developed paragraphs but instead, were reading shorter pieces, such as advertisements, interviews, or short articles. In addition, students might be unmotivated or uninterested in the type of readings that the ELT course books offer. This paper proposes extensive readings to be added to English courses that use ELT course books. This is because studies have shown that extensive reading can be helpful in developing the student’s vocabulary, reading rate, and reading comprehension. It may also increase the student’s interest and motivation in learning English.